(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
Starting from the case of embryos exchanged in the Pertini’s hospital in Rome, I take in consideration the Answer of the National Committee for the Bioethics and I move some criticism towards affirmations about the possibility to predispose a “bioethics instrument” for an eventual child-exchange after birth. I analyze the order of the Tribunal of Rome and the question of constitutionality proposed and rejected. At the end I propose a distinction between the legal interest to be protected in case of surrogacy and in the case of “heterologous fertilization by mistake” or “surrogacy by mistake”.